ANÁLISE DO PERFIL DE PROTEÍNAS DA LEVEDURA CATANDUVA-1 ATRAVÉS DE RECICLOS FERMENTATIVOS - AMORIM, Murilo Gonçalves de; SILVA, Rebeca Fasioli; MASCARENHAS SANTOS, Maria do Socorro; MUELLER, Larissa Pires; BATISTOTE, Margareth (ANAIS DO ENIC, 2018)
-